Two new species of Clinanthus (Asparagales: Amaryllidaceae: Clinantheae) from northern Peru - Gonzáles, Paúl; Meerow, Alan W. (Phytotaxa, 2020)
Clinanthus fabianae and C. thiagoi are described from Ancash and La Libertad departments of Peru. Both species have similar perigone coloration, broadly lobed staminal coronas, and incurved free filaments. They may represent a distinct species group, along with the previously described C. inflatus. The species can be separated by number of flowers, pedicel length, flower habit, tube length, morphology and pattern of dilation, and color of the tepal apiculum.